Menekan Turn Over Intention dengan Memaksimalkan Proses Rekrutmen pada UMKM Master Laundry Pekanbaru - Resti Riandi; Irsyadi Zain; Jusmarni (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
This community service activity aims to provide enlightenment in empowering human resources (employees) in a good work environment. The goal is to minimize employee turnover rates starting from the employee recruitment process, the attitudes of leaders and employees. In addition, there is also training in recording good and correct financial transactions. This service method uses seminars and training methods, the Community Service team is followed by a question-and-answer session from the audience. The seminar method provides an overview of how to become a leader who can influence his subordinates, training is used to apply what has been conveyed in the seminar. The material presented in this seminar discusses a good employee recruitment process by offering several stages of the employee recruitment process that are simple and commonly used. In addition to the employee recruitment process, material discussion is also directed to leaders and employees. Community Service Results as a whole the activity ran smoothly and it can be said that the participants were able to take part in the activity well. This activity involved lecturers from the Management study program in collaboration with Master Laundry as the target subject.